Legal Efforts by Consumer Financing Institutions Due to Financing Agreements with Fiduciary Guarantees through Application for Judicial Review of the Fiduciary Guarantee Law at the Constitutional Court - Rolib Sitorus; Permai Yudi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to find out how to obtain legal protection for consumer financing institutions or leasing companies, which the government has not paid much attention to in dealing with naughty debtors in the sense of having defaulted or broken promises in carrying out their obligations to creditors (consumer financing institutions/companies leasing). The presence of a financial institution is a business entity that provides financing by providing capital goods or funds through an installment system. Based on the Regulation of the President of the Republic of Indonesia Number 9 of 2009 concerning Financing Institutions. Financial institutions such asleasingis a form of business activity in the form of capital goods carried out through option rights or without option rights within a period according to the agreement between the creditor and the debtor. The object of the transaction is to become the property of the financing institution (creditor) during the validity of the leasing agreement with the consumer (debtor). Until the creditor or consumer has paid off his debt to the leasing company. The research method used to discuss this problem is normative juridical, normative juridical is a way of examining legal norms and rules in applicable laws and regulations (positive law), which is related to the topic of the problem being researched.